Audit of Antibiotic Prescribing Practices for Neonatal Sepsis and Measurement of Outcome in New Born Unit at Kenyatta National Hospital. (28th April 2019) - Tank, Priti Jagdishbhai; Omar, Anjumanara; Musoke, Rachel
Abstract : Background . Neonatal sepsis is a leading cause of morbidity and mortality globally. A high index of suspicion is required since features of sepsis are nonspecific. Auditing of antibiotic use is necessary to reduce misuse and minimise development of antibiotic resistance. Objectives . To assess the antibiotic prescribing practices in NBU at KNH against recommended Kenyan guidelines for neonatal sepsis. In addition, outcome within 7 days was described. Methods . This was a prospective audit of 320 neonates over a 2-month period at NBU of KNH. Data were collected using a structured questionnaire, stored in MS-EXCEL, and analysed using STATA. Results . Documentation of perinatal risk factors and clinical features at admission and at the time of change of antibiotics was very poor. The rate of investigations to confirm infection was very low. Blood cultures were done only in 13 (4%) neonates on admission, while complete blood count and C reactive protein were done in 224 (70%) and 198 (62%), respectively. Appropriate antibiotics as per the Kenyan guidelines were prescribed in 313 (97.8%) of neonates on admission. However, these were not stopped at 48-72 hours for the 148 (53.62%) who had improved. Overall mortality was high in neonates at 80 (25%). Majority (55%) died within 48 hours. Mortality was high among preterm neonates; 70 (43.8%) died out of 160. Conclusion . Overall documentation and investigations to confirm infection was poor. The continuation of antibiotics was inappropriate. Overall mortality was high especially in the first 48 hours of admission. To improve documentation, availability of a checklist on admission is recommended.